A "Cry of the Dying Century": Kate Chopin, The Awakening, and the Women’s Cause - Valkeakari, Tuire (Nordic Journal of English Studies, 2003)
Kate Chopin’s 1899 novel(la) The Awakening has elicited a multitude of scholarly responses since the beginning of the revival of Chopin studies at the end of the 1960s. Although feminist critics’ enthusiastic embrace of Chopin and her work has influenced The Awakenings reception across the divided terrain of literary criticism, current views of the novel’s position on the "women’s cause" still vary greatly. Some scholars categorically label the feminist readings of the text anachronistic.